Julião Sarmento’s Moving Images: Vision’s Perversity For The Maintenance of Desire - Marques, Bruno (2021)
This article analyses an audiovisual essay created around the exhibition Julião Sarmento. Film Works, that took place in Universidade Católica Portuguesa in Porto in 2019. This exhibition reunited 10 works in film and video produced by the Portuguese artist in different moments of his career. Following the audiovisual essay’s structure, I will approach three thematic obsessions transversal to Julião Sarmento’s work, as a reflexive proposal about a gaze phenomenology (or a vision’s perversity), regarding dispositives that involve the moving image. Particularly, in what concerns the problematic of desire. These are: (1) The constant work of language (the real, the symbolic and the imaginary); (2) The fragmented body (the conscience/disassembling of voyeurism); (3) The rhythm (exposing the matter of time in favor of a deceptive aesthetics).